Cancer stem cells are new vistas for predicting the course of breast cancer - E. A. Maslyukova; S. I. Zabroda; L. I. Korytova; K. M. Pozharissky; G. A. Raskin; O. V. Korytov (Опухоли женской репродуктивной системы, 2015)
Despite progress in treating breast cancer (BC) using a combined approach in view of morphological findings, distant metastases may develop in 30–90 % of patients with primary BC even at its early stages. The cancer stem cell (CSC) theory is one of the versions that could at least partially explain therapeutic inefficiency. This theory suggests that cancer may occur and arise from a small proportion of stem cells that are able to induce tumor growth and to affect resistance to chemoand radiotherapy. CSCs were identified in different malignant tumors, including BC, cancer of the prostate, colon, pancreas, head and neck, melanoma, and multiple myelomas. This investigation analyzed aldehyde dehydrogenase type 1 (ALDH1) expression in patients with BC. Moreover, the investigators examined the relationship between this marker and the clinical and pathological features of BC. The investigation enrolled 83 locally advanced BC (T1–4N0–3M0) patients treated in 2005 to 2009. To detect CSCs, 83 histological specimens obtained at biopsy in BC patients treated at the Russian Research Center for Radiology and Surgical Technologies underwent immunohistochemical examination for ALDH1 according to the developed protocol. Analysis of a relationship between time to metastases and ALDH1 expression showed a statistically significant decrease in time to disease progression in BC patients with high ALDH1 expression versus those with low ALDH1 expression. The similar trend was observed in overall survival. The survival of patients with less than 1 % ALDH1 expression in the cancer cells was statistically higher than that in the patients with high ALDH1 expression (more than 1 %).